Muslim women, transnational feminism and the ethics of pedagogy : contested imaginaries in post-9/11 cultural practice - Taylor, Lisa K.; Zine, Jasmin, 1963- (New York : Routledge, 2014)
'Following a long historical legacy, Muslim women's lives continue to be represented and circulate widely as a vehicle of intercultural understanding within a context of the'war on terror.' Following Edward Said's thesis that these cultural forms reflect and participate in the power plays of empire, this volume examines the popular and widespread production and reception of Muslim women's lives and narratives in literature, poetry, cinema, television and popular culture within the politics of a post-9/11 world. This edited collection provides a timely exploration into the pedagogical and ethical possibilities opened up by transnational, feminist, and anti-colonial readings that can work against sensationalized and stereotypical representations of Muslim women. It addresses the gap in contemporary theoretical discourse amongst educators teaching literary and cultural texts by and about Muslim Women, and brings scholars from the fields of education, literary and cultural studies, and Muslim women's studies to examine the politics and ethics of transnational anti-colonial reading practices and pedagogy. The book features interviews with Muslim women artists and cultural producers who provide engaging reflections on the transformative role of the arts as a form of critical public pedagogy.'--
pt. 1. Transnational anticolonial feminist reading practices -- pt. 2. The politics of production and reception -- pt. 3. Transformative pedagogies -- pt. 4. Reflections on cultural production.
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: Muslim women -- Social conditions -- Cross-cultural studies; Sex role -- Religious aspects -- Islam -- Cross-cultural studies; Islamic countries -- Study and teaching; Electronic books